Export Competitiveness of Indonesian Chocolate Drink Powder and Its Barriers and Challenges - Styawati, Anica; Sya'diah, Sri Djatnika (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Indonesia ranks among the world’s largest cocoa bean producers; however, its export value is largely confined to semi-processed products. Major importers like Malaysia and China possess advanced cocoa processing industries, importing Indonesian cocoa beans to produce higher-value products. While demand for processed cocoa in China has rapidly increased, Indonesia’s cocoa powder exports (HS Code 180610) to Malaysia and China from 2020 to 2024 have shown significant fluctuations, with competitiveness notably declining in the Chinese market. This study employs a mixed-methods approach, combining quantitative analysis using Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD), with qualitative insights from interviews with MSME stakeholders and the FTA Center. Findings reveal that Indonesia retains comparative advantage in Malaysia (RCA > 1), yet experiences stagnation or decline in competitiveness, identified as Lost Opportunity and Falling Star segments in the EPD matrix. Conversely, competitiveness in China deteriorates sharply due to decreasing market share. MSMEs face challenges such as stringent regulatory and certification demands, high logistics costs, and competition from industrial producers. Policy recommendations include enhancing downstream processing, innovating high-value products meeting international standards, diversifying export markets, and strengthening government support to boost Indonesia’s cocoa powder export competitiveness.